FENOMENA PRAKTIK CINGKRANG IMPLEMENTASI LARANGAN ISBAL (Studi Living Hadis Pada Masyarakat Muslim MangunharjoProbolinggo) - Irfan Yuhadi; Nurul Budi Murtini (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2020)
Clothing serves to cover the nakedness of Adam’s children and also as jewelry for them. A muslim should wear beautiful clothes, but should not be excessive and not accompanied by a sense of arrogance when wearing them. The term isbal means lengthening, anchoring and extending clothes to cover the ankles and touching the ground, either because of arrogance or not. Mangunharjo is one of the villages in Mayangan sub-district, Probolinggo, East Java. The formulations of the problem in this research are about: (1) the driving factor and the stages which are passed by a muslim in using his cingkrang (cropped) pants, (2) the challenges that are taken and the pleasure felt by a muslim after wearing a cingkrang (cropped) pants, (3) hadiths which prescribe a muslim to wear wearing a cingkrang (cropped) pants. The approach usedin this research is qualitative approach with the study of living hadith models. The results of this study indicate that: (1) There are 4 motivating factors for Mangunharjo’s muslims in wearing cingkrang (cropped) pantsand there are 5 stages that are passed by these muslims until they succeed in wearing it. (2) There are 5 challenges faced by muslims after wearing cingkrang (cropped) pantsand there are 4 of the toughest challenges they feel after they wearing it. On the other hand, they actually feel the 4 pleasures after they continue wearing it. (3) There are a number of hadiths which prescribe a muslim to wear cingkrang (cropped) pants as an implementation of the prohibition on isbal.